Concurrent chronic follicular conjunctivitis and conjunctival MALT lymphoma potentially caused by Chlamydia pneumoniae - Yueh-Ling Chen; Shih-Ming Jung; Ching-Hsi Hsiao (IDCases)
Chlamydia, particularly C. psittaci, has been implicated in the pathogenesis of ocular adnexal lymphoma with varying geographical prevalence. We report a patient with concurrent chronic follicular conjunctivitis and conjunctiva mucosa-associated lymphoid tissue (MALT) lymphoma, potentially caused by C. pneumoniae. A 30-year-old female presented with a 10-month history of persistent discharge from the left eye. Examination of the conjunctiva revealed large follicles and a salmon-patched lesion over inferior fornix. Chlamydial antigen testing from conjunctival swab was positive, so the patient underwent a 3-week course of oral doxycycline (100 mg, twice daily), after which the discharge resolved, but the conjunctival mass persisted. A subsequent conjunctival biopsy identified extranodal marginal zone lymphoma of MALT type. Following systemic evaluations, clinical staging indicated T1N0M0, stage IE. The patient received a total 3060 cGy of radiotherapy in 17 fractions, leading to regression of the lesion. Touchdown Enzyme Time-Release polymerase chain reaction analysis of formalin-fixed paraffin-embedded biopsy samples confirmed the presence of C. pneumoniae DNA. This case highlights a potential association between chronic follicular conjunctivitis and conjunctival MALT lymphoma, possibly linked to C. pneumoniae infection. The potential causality warrants further investigation.